Two rare cases of synchronous and metachronous colonic metastases in patients with advanced gastric cancer - Wei-Chih Su; Hsiang-Lin Tsai; Chun-Chieh Wu; Shan-Yin Tsai; Yung-Sung Yeh; Cheng-Jen Ma; Jaw-Yuan Wang (World Journal of Surgical Oncology, 2018)
Abstract Background Patients with advanced gastric cancer (GC) may ultimately die because GC mostly leads to synchronous or metachronous metastasis. However, colonic metastasis of GC is extremely rare. According to a PubMed search of papers published from May 1968 to March 2017, only 21 patients with GC (10 patients from 10 case reports and 11 patients from a retrospective study) have been found to have colonic metastasis. In this report, we present two cases of synchronous and metachronous colonic metastases of advanced GC. Case presentation Two patients with advanced GC received a diagnosis of colonic metastasis based on colonoscopic findings and computed tomography images, and the diagnosis was confirmed through pathological immunohistochemical analysis. Herein, we describe the management and outcomes of these metastases. Conclusions Submucosal swelling and segmental bowel wall thickening observed through colonoscopy in patients with advanced GC might indicate colonic metastasis.